Optimization approach of wireless power transfer systems for electric vehicles from a process and material perspective - Risch, Florian; Kraner, Sebastian; Schneider, Michael; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014 - Proceedings, 2014)
Modern Wireless Power Transfer (WPT) systems for electric vehicles (EVs) have already shown their potential for high-power transfer efficiency in many prototypes and trials. However, WPT for EVs is a particularly demanding application and still in its early commercialization phase. There are still some barriers to overcome for a successful and large-scale implementation of WPT systems to become a preferred method for recharging EVs. For practical application in an EV, power pads need to meet strict automotive requirements (ISO/TS 16949:2009 certification). A thorough material and process analysis must be used to identify and assess failure modes and effects preventatively. In this context, it is the objective of this paper to present an automated test bench approach to precisely evaluate WPT systems with a focus on the process and material perspective.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric vehicles; process and material parameters; test bench concept; wireless power transfer systems